2000
DOI: 10.1007/pl00005534
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry Breaking and Other Phenomena in the Optimization of Eigenvalues for Composite Membranes

Abstract: We consider the following eigenvalue optimization problem: Given a bounded domain ⊂ R and numbers α > 0, A ∈ [0, | |], find a subset D ⊂ of area A for which the first Dirichlet eigenvalue of the operator − + αχ D is as small as possible.We prove existence of solutions and investigate their qualitative properties. For example, we show that for some symmetric domains (thin annuli and dumbbells with narrow handle) optimal solutions must possess fewer symmetries than ; on the other hand, for convex reflection symm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
142
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(145 citation statements)
references
References 22 publications
0
142
0
3
Order By: Relevance
“…5. It has been discussed in [6], when the annulus becomes "thinner", the minimize density function of Problem 2.2 loses rotational symmetry, which is verified numerically in Fig. 5.…”
Section: Example 44mentioning
confidence: 62%
See 3 more Smart Citations
“…5. It has been discussed in [6], when the annulus becomes "thinner", the minimize density function of Problem 2.2 loses rotational symmetry, which is verified numerically in Fig. 5.…”
Section: Example 44mentioning
confidence: 62%
“…Problem 3.1 with two different materials over the disk has been considered in [6,24]. It was shown that in order to obtain the minimum, the material with high density has to be placed in the center of the disk and the remaining annulus is filled by the low density material.…”
Section: Numerical Examplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Surely, this method can also be applied to many other optimization problems, however, we should warn the readers that the method has its limitations. For example, in [3,4], the authors explore the possibility of designing a membrane, fixed at the boundary, and made out of two materials, so that the corresponding frequency is maximal. This is shape optimization problem to which the method of tangent cones can certainly be applied.…”
Section: Introductionmentioning
confidence: 99%